2019
DOI: 10.1111/dth.13054
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy and safety of fractional radiofrequency and fractional Er:YAG laser in facial and neck wrinkles: Six‐year experience with 333 patients

Abstract: Lasers and other light sources are popular treatment options for facial rejuvenation in recent years. In this study, we aimed to compare the efficacy and safety of fractional radiofrequency (RF) and fractional Erbium: YAG (Er:YAG) laser for facial and neck skin wrinkles, objectively. Three hundred and thirty‐three patients treated with fractional RF and fractional Er:YAG laser were evaluated by two blinded dermatologists. Fractional Er:YAG laser was more effective for the periorbital area; whereas fractional R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 13 publications
1
18
0
2
Order By: Relevance
“…Most trials used RF as the only intervention and compared it to baseline photography or untreated split-face. In other studies, RF was compared to laser (n = 8), [25][26][27][28][29][30][31] IPL (n = 1), 29 high-intensity focused ultrasound (n = 1), 11 microfocused ultrasound (n = 2), 32,33 BoNT/A (n = 1), 12 glycolic acid peels (n = 1), 13 LED (n = 1), 5 or facelift (n = 1). 34 These studies were included because they compared RF to baseline, providing information on the efficacy of RF alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most trials used RF as the only intervention and compared it to baseline photography or untreated split-face. In other studies, RF was compared to laser (n = 8), [25][26][27][28][29][30][31] IPL (n = 1), 29 high-intensity focused ultrasound (n = 1), 11 microfocused ultrasound (n = 2), 32,33 BoNT/A (n = 1), 12 glycolic acid peels (n = 1), 13 LED (n = 1), 5 or facelift (n = 1). 34 These studies were included because they compared RF to baseline, providing information on the efficacy of RF alone.…”
Section: Resultsmentioning
confidence: 99%
“…In general, studies that applied RF to the entire face had similar results as previously reported. RF was found to improve facial acne scars, 8,16 brow elevation, 6,55 periorbital rhytids, 16,17,53 lower face or neck rhytids, 6,26,68 Fitzpatrick wrinkle scale (FWC), 8 sagging of nasolabial folds, 13,16,53 skin laxity, 8,17,18,30,53,68,69 skin elasticity, 56,70 and overall skin aesthetic (e.g., pore size, texture, brightness, hydration). 8,14,17,25,56,70 RF was also found to be safe in darker skin types including Fitzpatrick V and VI.…”
Section: Retrospective Studymentioning
confidence: 99%
“…There were no occurrences of hematoma, seroma, infection, necrosis, contour irregularity, or other complications. The overall rate of adverse events was 7.4% which compares favorably with other procedures for neck rejuvenation 11,12 . Among subjects treated with percutaneous radiofrequency treating skin laxity under the chin and neck, common adverse events were hypoesthesia (30.56%), edema (22.22%), and swelling (11.11%) at the application site 13…”
Section: Discussionmentioning
confidence: 89%
“…79 Frequently reported adverse effects of RF include transient swelling, erythema, discomfort, and ecchymosis, which resolve in 1 to 5 days but there has been a reported case of RF microneedling-induced rosacea. 80,86,88 Patients usually tolerate treatments with none to mild discomfort and posttreatment discomfort usually resolves within 3 days. 86 Innovation and new uses of RF devices continue; further refinements in delivery systems to better target RF energy to the intended dermal target without damaging the surround tissue are being developed and refined including combining RF devices with lasers, microneedling, thermocontraction, targeted pressure energy, and fillers.…”
Section: Radiofrequencymentioning
confidence: 99%